Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3349/ymj.2009.50.3.358
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ovariectomy on Bone Turnover and Trabecular Bone Mass in Mature Cynomolgus Monkeys

Abstract: PurposeTo examine the influence of ovariectomy (OVX) on bone turnover and trabecular bone mass at the 3 clinically important skeletal sites in mature cynomolgus monkeys.Materials and MethodsSix female cynomolgus monkeys, aged 17-21 years, were randomized into 2 groups by the stratified weight: the OVX and sham-operation groups (n = 3 in each group). The experimental period was 16 months. Lumbar bone mineral density (BMD) in vivo and serum and urinary bone turnover markers were longitudinally measured, and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
(22 reference statements)
1
6
1
Order By: Relevance
“…These studies confirm that both long-term ovxed and anovulatory, ovary intact socially subordinate female marmosets are estrogen deplete, and demonstrate that this estrogen depletion is not associated with lower L5-6 bone mass. This observation is unique among female primates and contrasts with findings in other mammals (Bauss & Russell, 2004;Binkley et al, 1998;Colman et al, 1999;Florio et al, 2016;Havill et al, 2008;Iwamoto et al, 2009;Komori, 2015;Smith et al, 2009), including humans (Khosla, 2013;Khosla et al, 2012), in which estrogen reduction leads to bone loss. Elucidation of the mechanism(s) that prevent estrogendepletion bone loss in marmosets may provide important insight into approaches for preventing such loss in humans.…”
Section: Discussioncontrasting
confidence: 58%
“…These studies confirm that both long-term ovxed and anovulatory, ovary intact socially subordinate female marmosets are estrogen deplete, and demonstrate that this estrogen depletion is not associated with lower L5-6 bone mass. This observation is unique among female primates and contrasts with findings in other mammals (Bauss & Russell, 2004;Binkley et al, 1998;Colman et al, 1999;Florio et al, 2016;Havill et al, 2008;Iwamoto et al, 2009;Komori, 2015;Smith et al, 2009), including humans (Khosla, 2013;Khosla et al, 2012), in which estrogen reduction leads to bone loss. Elucidation of the mechanism(s) that prevent estrogendepletion bone loss in marmosets may provide important insight into approaches for preventing such loss in humans.…”
Section: Discussioncontrasting
confidence: 58%
“…2,3,31 Serum CTX-1 levels, a bone resorption marker associated with osteoclastic activity, showed significant elevation in all OVX groups compared with the control group, consistent with the study of Lai et al 32 Increased BMSC proliferation was shown in the 3M and 4M groups and increased osteoblastic differentiation was shown in the 4M group, which corresponded to previous studies using ovariectomized animals. [28][29][30] Interestingly, rats in the 4M group showed significantly higher ALP protein expression levels and much larger numbers of calcified nodules, indicating more accelerated osteoblastic differentiation than that in the other groups. In contrast, osteoclastic activity evaluated by actin ring staining and resorption pit assay showed a rapid decrease in the 4M group.…”
Section: F I G U R Ementioning
confidence: 93%
“…Several previous studies reported increased bone turnover rates in ovariectomized animals. [28][29][30] It is accepted that bone resorption exceeding bone formation leads to net bone loss. 2,3,31 Serum CTX-1 levels, a bone resorption marker associated with osteoclastic activity, showed significant elevation in all OVX groups compared with the control group, consistent with the study of Lai et al 32 Increased BMSC proliferation was shown in the 3M and 4M groups and increased osteoblastic differentiation was shown in the 4M group, which corresponded to previous studies using ovariectomized animals.…”
Section: F I G U R Ementioning
confidence: 99%
“…The skeletal characteristics of nonhuman primates and humans are believed to be similar, and experimental data acquired from nonhuman primates are generally allowed to be extrapolated to humans 2 . Cynomolgus monkeys have monthly menstrual cycles, reproductive hormone patterns, and bone metabolism similar to those of humans, and ovariectomized (OVX) female monkeys are widely used as models for postmenopausal osteoporosis 3 , 4 , 5 . Peak bone mass in the lumbar spine of the female cynomolgus monkey is likely achieved by 9 years of age, and female monkeys 9 years of age or older are recommended for use in osteoporosis investigations 6 .…”
mentioning
confidence: 99%
“…Peak bone mass in the lumbar spine of the female cynomolgus monkey is likely achieved by 9 years of age, and female monkeys 9 years of age or older are recommended for use in osteoporosis investigations 6 . Although skeletally mature OVX monkeys have been proven to be appropriate experimental models 5 , acquisition of aged monkeys is difficult and very costly 4 .…”
mentioning
confidence: 99%